2021
DOI: 10.1177/21501351211014824
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury After Neonatal Aortic Arch Surgery: Deep Hypothermic Circulatory Arrest Versus Moderate Hypothermia With Distal Aortic Perfusion

Abstract: Background: Acute kidney injury (AKI) is a common complication observed after neonatal aortic arch repair. We studied its incidence after procedures carried out using deep hypothermic circulatory arrest (DHCA) versus moderate hypothermia with distal aortic perfusion (MHDP), usually through the common femoral artery. In both groups, continuous regional cerebral perfusion (RCP) was used during the time required for aortic arch repair. Methods: A total of 125 neonates underwent aortic arch repair. Between 2007 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This is also consistent with the finding that intra- and postoperative 4th to 6th h lactate level is an independent predictor of early mortality. Böttcher et al,[ 17 ] in their study, reported that the use of moderate hypothermia with distal aortic perfusion was associated with a significantly lower incidence of kidney injury. On the other hand, Kulyabin et al[ 18 ] reported that double arterial cannulation did not reduce the acute kidney injury incidence, compared to deep HCA.…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with the finding that intra- and postoperative 4th to 6th h lactate level is an independent predictor of early mortality. Böttcher et al,[ 17 ] in their study, reported that the use of moderate hypothermia with distal aortic perfusion was associated with a significantly lower incidence of kidney injury. On the other hand, Kulyabin et al[ 18 ] reported that double arterial cannulation did not reduce the acute kidney injury incidence, compared to deep HCA.…”
Section: Discussionmentioning
confidence: 99%
“…Many ischemic events can be anticipated with opportunities to prevent ischemic injury. For example, major cardiovascular surgeries including repair of the ascending or abdominal aorta, coronary revascularization, and heart valve surgery may lead to ischemic injury of the heart, brain, and kidneys ( Naito et al, 2020 ; Böttcher et al, 2021 ). In addition, organs harvested for transplantation including hearts, kidneys, livers, and lungs are all subject to ischemic injury ( Naito et al, 2020 ).…”
Section: Gja1-20k Induces Protective Mitochondrial Fissionmentioning
confidence: 99%
“…The extent of ischemic injury in such surgeries is minimized by limiting the ischemic time and packing organs in ice ( Naito et al, 2020 ). However, ischemic injury remains a common complication ( Naito et al, 2020 ; Böttcher et al, 2021 ).…”
Section: Gja1-20k Induces Protective Mitochondrial Fissionmentioning
confidence: 99%